2023
DOI: 10.3390/ph16091193
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and Antioxidant Drugs in Glaucoma Treatment

Francesco Buonfiglio,
Norbert Pfeiffer,
Adrian Gericke

Abstract: Glaucoma, a group of diseases characterized by progressive retinal ganglion cell loss, cupping of the optic disc, and a typical pattern of visual field defects, is a leading cause of severe visual impairment and blindness worldwide. Elevated intraocular pressure (IOP) is the leading risk factor for glaucoma development. However, glaucoma can also develop at normal pressure levels. An increased susceptibility of retinal ganglion cells to IOP, systemic vascular dysregulation, endothelial dysfunction, and autoimm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 265 publications
0
6
0
Order By: Relevance
“…Traditionally, primary glaucoma has been viewed as a disorder of ocular hypertension. However, recent research has broadened this view to include the role of immune dysregulation in the pathogenesis of the disease [11,12,32]. The relationship between AS and primary glaucoma is complex and not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, primary glaucoma has been viewed as a disorder of ocular hypertension. However, recent research has broadened this view to include the role of immune dysregulation in the pathogenesis of the disease [11,12,32]. The relationship between AS and primary glaucoma is complex and not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pathogenesis of RGC loss may be multifactorial, involving factors such as autoimmune response, oxidative stress, mitochondrial dysfunction, and aging, in addition to elevated intraocular pressure [4][5][6][7][8]. In recent years, more and more research has revealed the link between immune factors and glaucoma, and immune-mediated neurodegeneration is considered to be an important component of the pathogenesis of glaucoma [9][10][11][12]. Chen H et al demonstrated that T-cell in ltration can lead to chronic degenerative changes in retinal ganglion cells, and Heat shock proteins (HSP) are target antigens of T-cell response.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the fundoscopic signs of glaucoma-an enlarged optic cup, an increased cup-disc ratio, the loss of the neuroretinal rim, the presence of disc hemorrhages, and parapapillary tissue atrophy-assessing the disease progression can be achieved through a spectral-domain optical coherence tomography evaluation of the optic disc and visual field analysis [16]. The primary objective of the treatment of glaucoma is to reduce the intraocular pressure in order to halt the progression of the disease [17]. The treatment of glaucoma is primarily oriented toward lowering the intraocular pressure with medicaments, lasers, or incisional glaucoma surgery [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, glaucoma treatment development has focused on reducing IOP. However, controlling IOP alone does not entirely prevent RGC loss [4] . Persistent deterioration of optic nerve function may occur after treatment, so protection of RGC damage is also key to glaucoma treatment.…”
Section: Introductionmentioning
confidence: 99%